Effect of Vacuum Frying on Changes in Quality Attributes of Jackfruit (Artocarpus heterophyllus) Bulb Slices - Tanushree Maity; A. S. Bawa; P. S. Raju (International Journal of Food Science)
The effect of frying temperatures and durations on the quality of vacuum fried jackfruit (JF) chips was evaluated. Moisture content and breaking force of JF chips decreased with increase in frying temperature and time during vacuum frying whereas the oil content increased. The frying time for JF chips was found to be 30, 25, and 20 minutes at 80, 90, and 100°C, respectively. JF chips fried at higher temperature resulted in maximum shrinkage (48%). The lightness in terms of hunter L* value decreased significantly (P<0.05) during frying. Sensory evaluation showed maximum acceptability for JF chips fried at 90°C for 25 min. Frying under vacuum at lower temperatures was found to retain bioactive compounds such as total phenolics, total flavonoids, and total carotenoids in JF chips. Almost 90% of carotenoids were lost from the samples after 30 min of frying at 100°C.